2005
DOI: 10.1007/s10350-004-0932-1
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Outcomes Evaluation of Mucinous and Signet-Ring Cell Carcinoma of the Colon and Rectum

Abstract: We present a large population-based review of colorectal cancer subtypes by analyzing national data from the past decade. Although the incidence of colorectal adenocarcinoma is decreasing in the United States, mucinous and signet-ring cell subtypes are stable and increasing, respectively. Importantly, it seems that the signet-ring cell subtype has worse outcomes, whereas survival rates for mucinous tumors are similar to adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

37
257
9
18

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(321 citation statements)
references
References 21 publications
(19 reference statements)
37
257
9
18
Order By: Relevance
“…The reported 5-year survival in the literature is 9-37%, [1][2][3][4][5][6][7][8][9][10] which is comparable to the 33% survival in this study. The literature contains limited data on the molecular features of signet ring cell carcinoma.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The reported 5-year survival in the literature is 9-37%, [1][2][3][4][5][6][7][8][9][10] which is comparable to the 33% survival in this study. The literature contains limited data on the molecular features of signet ring cell carcinoma.…”
Section: Discussionsupporting
confidence: 84%
“…[1][2][3][4][5][6][7][8][9][10] By definition, 450% of tumor cells have signet ring cell morphology. 11 Signet ring histology is considered an independent adverse prognostic factor by the American Joint Committee on Cancer and the College of American Pathologists.…”
mentioning
confidence: 99%
“…On the other hand, other studies did not confirm the worse prognosis in patients with MA compared to NMA of the colon [19,24]. An analysis from the National Cancer Database showed inferior OS in MA of the rectum but not of the colon [9].…”
Section: Discussionmentioning
confidence: 92%
“…According to Simonds et al and Umpleby et al, mucin should constitute at least 60% of the colonic cancer specimen to be labeled as MA [16,17], while a cutoff level of 50% is being used in WHO classification [18]. This difference in cutoff value may explain the higher incidence of MA in the western countries compared to those in Asia [16,19]. Many studies showed that patients with MA of the rectum had worse prognosis in terms of RFS and OS compared to non-mucinous adenocarcinoma (NMA) [9,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation